2001
DOI: 10.1046/j.1365-2036.2001.00974.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic comparison of triple therapies for treatment of Helicobacter pylori infection with proton pump inhibitor/ ranitidine bismuth citrate plus clarithromycin and either amoxicillin or a nitroimidazole

Abstract: Background: Triple therapies with proton pump inhibitor/ranitidine bismuth citrate (RBC), clarithromycin (C) and either amoxicillin (A) or a nitroimidazole (I) are widely accepted as treatment for Helicobacter pylori infection. However, it is not clear which of these antibiotic combinations should be preferred. Aim: To evaluate whether there is a difference in efficacy between triple therapies with proton pump inhibitor/RBC, clarithromycin and either amoxicillin or a nitroimidazole. Methods: The literature was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 69 publications
0
40
0
Order By: Relevance
“…85 RBC-based, triple regimens containing F were as efficient as the PPI-based therapies: this is in agreement with the meta-analysis which showed that RBC-based standard triple therapies achieved PER of 73-83%, [80][81][82] and in direct comparative trials, the OR for RBC versus PPI-based therapies was 1.15 (CI 0.8-1.64). 86,87 The number of studies and patients included in our study was rather small, and in fact RBC is recommended as first-line therapy only in the 2nd Maastricht consensus, 6 it is not mentioned in the AsianPacific and Latin-American statements 8,9 and its availability in these areas is rather limited.…”
Section: Discussionmentioning
confidence: 99%
“…85 RBC-based, triple regimens containing F were as efficient as the PPI-based therapies: this is in agreement with the meta-analysis which showed that RBC-based standard triple therapies achieved PER of 73-83%, [80][81][82] and in direct comparative trials, the OR for RBC versus PPI-based therapies was 1.15 (CI 0.8-1.64). 86,87 The number of studies and patients included in our study was rather small, and in fact RBC is recommended as first-line therapy only in the 2nd Maastricht consensus, 6 it is not mentioned in the AsianPacific and Latin-American statements 8,9 and its availability in these areas is rather limited.…”
Section: Discussionmentioning
confidence: 99%
“…7 A large variation in efficacy exists between studies in these treatments regimens, with 95% CI ranging from 71 to 96% for ranitidine bismuth citrate triple therapies, and from 24 to 100% for PPI triple therapies. 8 Furthermore, triple and quadruple therapies seem to be also roughly equivalent in terms of effectiveness when administered as first-line treatment. 17 Subsequent second-line therapy should use quadruple therapy with a PPI, bismuth, metronidazole and tetracycline, but a recent review on rescue regimens reported as the weighted eradication mean with this rescue treatment was of 77.2% 18 Therefore, it remains a therapeutic dilemma which treatments using in those 20-30% of patients still infected after two eradication courses.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] However, the efficacy of these treatments is often well below the 90% of eradication rate according to intention-to-treat (ITT) analysis. 8 Treatment failures occur principally because of poor patient compliance or bacterial resistance. 9 As suggested from the Maastricht 2000 Consensus Report, subsequent second-line therapy should use quadruple therapy with a PPI, bismuth, metronidazole and tetracycline or a triple therapy changing one antibiotic (metronidazole instead of amoxicillin, or vice versa).…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years the efficacy of the standard first-line triple therapy has also been decreasing dramatically, mainly due to development of resistance to the drugs (35,59). Failure to cure H. pylori infection has been noted for more than 20 to 30% of patients (37). In addition, several studies have found an eradication rate lower than 75% (6,11,59), and values as low as 25 to 45% have also been recently reported (22,24).…”
mentioning
confidence: 99%